Community Satisfaction Survey in “Widodaren” Community Health Center - Tutiek Herlina (Journal of Global Pharma Technology, 2020)
Introduction: Community Health Center as health service unit that was the forefront of basic health services was expected to provide quality health services in accordance with community needs. Widodaren Community Health Center was one of Community Health Center in Ngawi Regency area which since 2015 has a full “BLUD” (Regional Public Service Agency) status, and all villages were still in pra advisory villages status. To saw how much quality of health services, it was necessary a Community Satisfaction Survey (CSS). The purpose of implementing CSS was to measure level of community satisfaction with basic health services by the Widodaren Community Health Center, Ngawi Regency in 2019. Community Health Center as health service unit that was the forefront of basic health services was expected to provide quality health services in accordance with community needs. Widodaren Community Health Center was one of Community Health Center in Ngawi Regency area which since 2015 has a full “BLUD” (Regional Public Service Agency) status, and all villages were still in pra advisory villages status. To saw how much quality of health services, it was necessary a Community Satisfaction Survey (CSS). The purpose of implementing CSS was to measure level of community satisfaction with basic health services by the Widodaren Community Health Center, Ngawi Regency in 2019. Methods: This research was survey. Samples were part of community who use health services at Widodaren Community Health Center who were selected by quota sampling technique. Variables studied were the level satisfaction of health services provided community health center. Collecting data with questionnaire. Data analysis with calculating the Community Satisfaction Index. Presentation of data in the form of tables and spider web diagrams. Results: The results showed that there was an influence of the physical activity model (Gambo Rasa) on blood glucose levels of type-2 diabetes mellitus. Results of this research are the service quality in all service units was above the target of 85, and an average of 88.187. Six service units were in excellent category and three service units in good category. Service quality based on service dimensions was above the target of 3,395 and an average of 3,530. Discussion and Conclusion: Four dimensions in excellent category and five dimensions in good category. The service quality of Widodaren Community Health Center in all service units and all dimensions are in good and excellent categories. As an effort to improve quality services, it is necesarry survey of needs or expectations of the latest, and satisfaction survey in 2020 as an evaluation of quality improvement efforts that have been made based on the results of CSS at 2019. Keywords: Survey, Satisfaction, Community, Service, Community Health Center